Analisis Hubungan Persepsi Mutu Pelayanan Antenatal Terhadap Kepuasan Ibu Hamil Di Puskesmas Bangetayu Kota Semarang Tahun 2014 - Mumpuni Sari Kusumastuti; Ayun Sriatmi; Sutopo Patria Jati (Jurnal Kesehatan Masyarakat (Undip), 2014)
>One of efforts for reducing maternal mortality rate (AKI) was done by improving the service quality.  The service quality  of  ANC  constitutes  demands of  society, thus within its capacity in health centers, midwives are demanded to be able to provide the better service quality of ANC in order to provide maternal satisfaction. From several health centers in Semarang City, the maternal mortality rate is high in  Bangetayu  health  centers.  The  high  mortality  rate  was  due  lack  of  optimal service  quality,  thus  affecting  the  level  of  maternal  satisfaction.  This  research aimed  to  analyze  the  relationship  of  antenatal  service  quality  –  which  includes perception of reliability, responsiveness, assurance, empathy and physical proofs with thesatisfaction of pregnant women in Bangetayu Semarang health center. Population  is  pregnant  women  who  perform  checks  in  Bangetayu  Semarang health by 2.330, with a sample of 96 respondents. Data analysis was performed using univariate and bivariate analysis chi-square test. The test results showed that the perception of reliability has a relationship with the satisfaction of pregnant women (p-value = 0.000). Perception of responsiveness has a relationship with maternal satisfaction (p-value = 0.000). Perceptions of warrant has a relationship with the satisfaction of pregnant women (p-value = 0.000). Perception of empathy has  a  relationship  with  the  satisfaction  of  pregnant  women  (p-value  =  0.000). Perceptions  of  the  physical  proof  has  a  significant  relationship  with  the satisfaction of pregnant women (p-value = 0.000). By the proven results of this research, it is necessary to improve the quality of antenatal service speed, so that pregnant  women  need  not  to  wait  too  long,  as  well  as  midwives  empathy  in providing explanation of the benefits of the drug to the pregnant women